Predominantly BCR-ABL negative myeloid precursors in interferon-α treated chronic myelogenous leukemia: a follow-up study of peripheral blood colony-forming cells with fluorescence in situ hybridization - Sick, Christoph; Schultheis, Beate; Pasternak, Günter; Kottke, I.; Hörner, Susanne; Heissig, Beate; Hehlmann, Rüdiger (Annals of hematology, 2001)
The mechanism and target cell of the life-prolonging effect of interferon-α (IFN-α) in chronic myelogenous leukemia (CML) are controversial. We studied the influence of IFN-α treatment on the frequency of malignant hematopoietic precursor cells in the peripheral blood (PB) of CML patients during the course of the disease. PB 10-day colony-forming cells (PB-CFCs) were assessed with regard to their quantity, lineage distribution, and BCR-ABL status, as determined by fluorescence in situ hybridization (FISH). PB-CFC numbers were determined in 39 patients (29 in the chronic phase, 6 in an advanced stage, and 4 with progression to an advanced stage during follow-up). Thirty-one patients were evaluated either once or several times to determine the BCR-ABL status of the colonies. BCR-ABL negative PB-CFCs were detectable at diagnosis in 5 of 11 patients. A major reduction of BCR-ABL positive colonies to <25% of PB-CFCs was observed in 10/13 determinable IFN-α treated patients in early and late chronic phases, indicating a high proportion of BCR-ABL negativity at the clonogenic cell level. In contrast, only 3 of these patients had a cytogenetic response of <25% Philadelphia chromosome (Ph1)-positive metaphases in bone marrow cytogenetics. Treatment with IFN-α and/or hydroxyurea (HU) during chronic phase was accompanied by a reduction of PB-CFCs to subnormal levels (median 24 CFCs/ml) compared to controls (median 207 CFCs/ml), untreated patients in chronic phase (median 25,979 CFCs/ml), and patients with advanced disease (median 6,047 CFCs/ml). In blast crisis (6 patients), all colonies tested were BCR-ABL positive. Our results show that IFN-α treatment leads to a marked reduction of malignant myeloid precursor cells in the PB of CML patients, which exceeds the degree of cytogenetic remission. This offers an explanation for the good therapeutic efficacy and even life-prolonging effect of IFN-α, which is also observed in cytogenetic non-responders.
Gesehen am 17.05.2022